A Perspective Emphasizing Circadian Rhythm Entrainment to Ensure Sustainable Crop Production in Controlled Environment Agriculture: Dynamic Use of LED Cues - Marie, Telesphore R. J. G.; Leonardos, Evangelos D.; Lanoue, Jason; Hao, Xiuming; Micallef, Barry J.; Grodzinski, Bernard (Frontiers in Sustainable Food Systems, 2022)
World-wide, sustainable crop production is increasingly dependent on the protection of crops from adverse local climate conditions by using controlled environment agriculture (CEA) facilities. Today’s greenhouses and plant factories are becoming very technologically advanced. Important breakthroughs in our understanding of the deployment of affordable artificial lighting systems that can supplement and even replace solar radiation is the subject of this perspective article. The key to improving sustainable CEA is to synchronize those environmental cues that best entrain the natural circadian rhythm of the crop. Patterns of circadian rhythms reflect the balance of daily metabolic cycles and phenological stages of development that integrate and anticipate environmental changes for all complex organisms. Within the last decade, our understanding of the use of light-emitting diodes (LEDs) as spectrally tunable tools for stimulating plant responses has expanded rapidly. This perspective proposes that extending the photoperiod in CEA is an economically sustainable goal to for year-round productivity of tomato, using dynamic LED shifts that entrain the circadian rhythm. When the photoperiod is extended too far, tomato experiences injury. To avoid yield reduction, we look to nature for clues, and how circadian rhythms evolved in general to long-photoperiods during the summer in high-latitudes. It follows that circadian rhythm traits are good targets for breeders to select new tomato cultivars suitable for CEA. Circadian rhythm entrainment, using dynamic LED cues, can be tailored to any latitude-of-origin crop, and thus expands the strategies ensuring sustainable food security including healthy diets locally in any region of the world.